Autolytic debridement and management of bacterial load with an occlusive hydroactive deressing impregnated with polyhexamethylene biguanide - Mancini, Stefano; Cuomo, Roberto; Poggialini, Mauro; D'Aniello, Carlo; Botta, Giuseppe (Acta Biomedica Atenei Parmensis, 2018)
Background: Debridement and control of bacterial load are key-points of wound care. The aim of this study is to evaluate the effectiveness of autolytic debridement and management of bacterial load (bioburden) of an occlusive hydro-active dressing impregnated with polyhexamethylene biguanide (PHMB). Methods: We used an occlusive dressing of hydro-active for leg ulcers’ treatment (TenderWet-plus® – Hartmann).  Inclusion criteria were: presence of a fibrinous ulcer with multiple etiopathogenesis, in absence of clinical infection, no hypersecretion and diameter within 5 cm. Swab for bacterial bioburden control were made at start of the study, after 3 and 7 days. We made also a measurement of the amount of granulation tissue and of pain with VAS scale; bacterial bioburden control inside the dressing was made too. Results: 28 leg ulcers were treated (12 venous, 5 diabetic, 8 thraumatic, 3 mixed) in 25 patients. The ulcer has been completely covered with fibrin in almost all cases and the bacterial load was represented mainly by Staphylococcus aureus (80% of the cases) with a load within 10.000UFC/plate in 81,5% of the cases. Control at 3 and 7 days have shown the appearance of granulaton tissue up to 67,8% of the wound surface. Bacterial bioburden (load) remained constant in 50% of the cases, decreased in 15%, increased in 35% of the cases. Conclusion: TenderWet-plus® has proven to be effective and quick in autolytic debridement and at the same time be able to handle the bacterial load in most cases. It can then be used for home treatment.